A concepção de professores dos anos iniciais do ensino fundamental sobre a construção do conceito de número pela criança - Silva, Ana Paula Perovano dos Santos (2012)
The present study aims to investigate concepts that are present when teachers proposes work the concept of number with students from 1st and 2nd years of elementary school of the Jequié BA. For both, we theoretical uses a framework that allows us to analize the number perspective: Mathematics Education emphasizing the ideas of Piaget and Kamii and Public Policy, translated in this work for the official documents, PCN, RCNEI and Curriculum Guidelines of the State of Bahia. To treat the optical of the teacher we add to this reflection, knowledge and conceptions of knowledge teachers. Developed research in a descriptive qualitative approach in with participated as subjects 13 teachers of the early years of elementary school for three scholls in the city of Jequié BA. Data collection was made though a questionnaire and semistructured interview. As a results of this process of reflection, it appears that the teachers have the idea that number is synonymous with the numeral, perform, too empirical evidence of design, trends and approaches of classical and formalistic socioetnocultural. That confusion may be reflected upon education implying a limition of teaching, restricting the number to work with the activities of reading and writing numerals. Hope helpin bringing ideas to teachers in relation to the construction of the concept of number for the child